2021
DOI: 10.1590/s1984-296120201082
|View full text |Cite
|
Sign up to set email alerts
|

Hippoboscid flies (Diptera: Hippoboscidae) on birds of prey in the Atlantic Forest, Minas Gerais, Brazil

Abstract: Hippoboscid flies are potential ectoparasites of several avian orders, including birds of prey, a group formed by the orders Falconiformes, Strigiformes, Cathartiformes and Accipitriformes. In this study, we evaluated 155 birds of prey that were brought to the Wildlife Rehabilitation Center of Juiz de Fora, Minas Gerais, Brazil, between the years 2016 and 2019. Two species of hippoboscid flies (Ornithoctona erythrocephala and Icosta americana) were found in five species of birds of prey (Megascops choliba, Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Hippoboscids flies are parasites usually associated with birds of prey (Accipitriformes, Cathartiformes, Falconiformes and Strigiformes) and pigeons (Columbiformes). Although less frequent, in Brazil hippoboscids were also collected on Passeriformes, Piciformes and Galliformes (Moreira et al, 2019, Vélez et al, 2020Gomes et al, 2021), corroborating other studies (Murgas et al, 2014;Barino et al 2021;Graciolli, Bispo, 2005;Graciolli and Oak, 2003;Liébana et al, 2011).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Hippoboscids flies are parasites usually associated with birds of prey (Accipitriformes, Cathartiformes, Falconiformes and Strigiformes) and pigeons (Columbiformes). Although less frequent, in Brazil hippoboscids were also collected on Passeriformes, Piciformes and Galliformes (Moreira et al, 2019, Vélez et al, 2020Gomes et al, 2021), corroborating other studies (Murgas et al, 2014;Barino et al 2021;Graciolli, Bispo, 2005;Graciolli and Oak, 2003;Liébana et al, 2011).…”
supporting
confidence: 86%
“…In agreement with a previous study conducted in 155 birds of prey received in a rescue center in Minas Gerais, Brazil, the parasitism by Ornithoctona erytrocephala and Icosta americana reposted. (Barino et al, 2021). Vaz and Teixeira (2016) and Moreira et al (2019) reported parasitism by Ornithoctona erytrocephala and Icosta americana in avian, occurring in the Brazilian South and Southeast regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Live-animal trapping is commonly used for wild animals, but current studies trap one or two host species as part of a larger focus (Pirrello et al 2015, Bezerra-Santos et al 2021, Levesque-Beaudin and Sinclair 2021 or continue to use randomness of roadkill or road injury cases to obtain samples (McAllister et al 2018(McAllister et al , 2019Lavallée et al 2020). Involvement of regional zoological medicine service or wildlife rehabilitator, often raptor rehabilitation centers, to identify regional ectoparasite-host relationships provide collections in an environment where the animal can be treated and released again into the wild (Morishita et al 2001, Barino et al 2021, Gherardi et al 2021). This study demonstrated direct usefulness of such a clinic to define new host relationships in the region as well as new records for ectoparasites in the state.…”
Section: Strigiformes: Barred Owl (Strix Varia Bartonmentioning
confidence: 99%